Studi Qana’ah sebagai Media Penghilang Stres - Khalikurrahman (Gunung Djati Conference Series, 2023)
Humans are creatures that have a mind and a soul. In addition to the physical state, humans must also maintain the state of the soul or we usually call it mental. One thing that can interfere with human mental health is stress. This research aims to provide solutions for people who experience stress so they can lead a more relaxed life and easily feel happiness in their lives. This study uses a qualitative method with descriptive-analytical. The object of this research is people who experience stress. The results and discussion of this study are that qanaah can be a solution for people who often experience stress. Qanaah is one of the attitudes in Sufism which teaches to accept things that come with a happy heart. The nature of qanaah is a lifestyle lived by people who want to get rid of stress in their lives so that they can accept everything that comes with an open heart.